Mucosal Adhesive Chitosan Nanogel Formulations of Antibiotics and Adjuvants (Terpenoids, Flavonoids, etc.) and Their Potential for the Treatment of Infectious Diseases of the Gastrointestinal Tract - Igor D. Zlotnikov; Natalya G. Belogurova; Irina V. Poddubnaya; Elena V. Kudryashova (MDPI AG, 2023)
Bacterial infections are usually found in the stomach and the first part of the small intestine in association with various pathologies, including ulcers, inflammatory diseases, and sometimes cancer. Treatment options may include combinations of antibiotics with proton pump inhibitors and anti-inflammatory drugs. However, all of them have high systemic exposure and, hence, unfavorable side effects, whereas their exposure in stomach mucus, the predominant location of the bacteria, is limited. Chitosan and nanogels based on chitosan presumably are not absorbed from the gastrointestinal tract and are known to adhere to the mucus. Therefore, they can serve as a basis for the local delivery of antibacterial drugs, increasing their exposure at the predominant location of therapeutic targets, thus improving the risk/benefit ratio. We have used E. coli ATCC 25922 (as a screening model of pathogenic bacteria) and Lactobacilli (as a model of a normal microbiome) to study the antibacterial activity of antibacterial drugs entrapped in a chitosan nanogel. Classical antibiotics were studied in a monotherapeutic regimen as well as in combination with individual terpenoids and flavonoids as adjuvants. It has been shown that levofloxacin (LF) in combination with zephirol demonstrate synergistic effects against E. coli (cell viability decreased by about 50%) and, surprisingly, a much weaker effect against Lactobacilli. A number of other combinations of antibiotic + adjuvant were also shown to be effective. Using FTIR and UV spectroscopy, it has been confirmed that chitosan nanogels with the drug are well adsorbed on the mucosal model, providing prolonged release at the target location. Using an ABTS assay, the antioxidant properties of flavonoids and other drugs are shown, which are potentially necessary to minimize the harmful effects of toxins and radicals produced by pathogens. In vivo experiments (on sturgeon fish) showed the effective action of antibacterial formulations developed based on LF in chitosan nanogels for up to 11 days. Thus, chitosan nanogels loaded with a combination of drugs and adjuvants can be considered as a new strategy for the treatment of infectious diseases of the gastrointestinal tract.